Reading and Responding to "English" Literature - Bakdi Soemanto (TEFLIN Journal: A publication on the teaching and learning of English, 1997)
Abstract: Literature is a performance in words, something to experience to see, hear, smell, feel and taste. It is a human, mental experience, a process of familiarizing the unfamiliar. In teaching literature let students be involved in the experience and let them observe life more closely.